THE ROLE OF THE WELL WATERS OF THE MAUSOLEUM OF KHOJA AHMED YASAVI IN THE FORMATION OF SALTS - Akbasova Amankul Dzhakanovna,; Aubakirov Nurimzhan Parzhanovish,; Anarbekova Gulchat Dzhumabaevna,; Sainova Gaukhar Askerovna, (Academic Journal of Physical and Chemical Sciences, 2020)
The work is devoted to the study of the chemical composition of well waters located on the territory of the mausoleum complex of Khoja Ahmed Yasavi. On the basis of experimental studies, the salinity of well waters increases every year. It is especially different in 2019 when, compared to the previous 10 years (2009-2018), there was a sharp increase in the total salt content by 1,5 times in the inner well and about 2,3 times in the outer well. The reason for this is the intense pollution of atmospheric air, soil, plants and other environmental objects due to an increase in the volume of construction work resulting from this waste, the number of servicing vehicles and the emergence of a number of new anthropogenic factors. The article also considers data from the Kazhydromet of the Republic of Kazakhstan that characterize changes in natural and climatic conditions, exactly, the amount of precipitation by month. Based on the calculated data, we have shown that water evaporation is 4-5 times higher than the amount of precipitation in the region. As a result of evaporation, moisture rises through the capillaries and is further saturated with salts found in building materials. Further, the formed saturated salt solution, undergoing various transformations, such as crystallization, contributes to the formation of salt deposits on the surface of the foundation materials and further walls. This negative phenomenon is one of the factors that lead to a decrease in the stability and safety of the architectural monument.